The use of the principle of sharing and mutuality in covering risks (in the modern world) - Krzysztof Łyskaw; Marietta Janowicz-Lomott (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: Operational risks appear as the main threats of the modern world. Mistakes made by employees, an imperfect information systems or changes in the law can cause losses that businesses today are not even able to estimate. Therefore, in the face of widespread the asymmetry of information, it becomes crucial to find such forms of financing losses, where the transmission of this information will not cause any concern. Such a form of insurance is based on the principle of mutuality. Design/methodology/approach: The research was based on a review of the literature in the area of asymmetric information and verification of research in the identification of key risk categories. Findings: Many researchers, including Nobel Prize winners, have identified the problem associated with a lack or asymmetry of information. But today, this issue leads to critical risks for businesses. This phenomenon is a subject of disclosure in the form of various categories of operational risk. Research limitations/implications: Mutuality-based insurance is therefore a path based on solutions of the past (primary forms of insurance), but at the same time is seen as a response to the lack of adaptation of insurance products to the actual needs of clients. Consequently, the agency theory (principal-agent dependency) commonly used in modern times is being replaced by the idea of a sharing economy. Originality/value: The study addresses a complex area of the modern economy. Companies run their business and they want to have adequate insurance products to cover possible losses, including operational risks. Today, the insurance market is not ready to build appropriate products. Only insurance based on mutuality and the realization of the sharing economy can allow the preparation of adequate insurance products.
Keywords: G32; G22; D82; 330; Operational risk; insurance; mutual insurance; asymmetry of information; agency theory